2014
DOI: 10.1002/crat.201300281
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the crystal structure at the relaxor ferroelectric phase transition of strontium barium niobate (SBN53)

Abstract: The average crystal structures of the ferroelectric and the intermediate paraelectric phases of SBN53 were refined at various temperatures up to 200 °C from single crystal X‐ray diffraction data. Shifts of the atoms reduce the microscopic spontaneous electric polarization which, however, does not entirely vanish on heating at the ferroelectric (FE) phase transition near 95 °C. Most atoms show an unusual temperature dependence of the atomic displacement parameters (adp). At the FE transition, a very large aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The change in Nb ADPs is clearly associated with the paraelectric (PE) phase transition. Graetsch investigated the room-temperature structure of SBN with a wide composition range ( x = 0.32–0.82) and reported an U 33 increase of ∼0.03 Å 2 when comparing the structures of the FE and the RE compositions ( x = 0.69 and 0.81, respectively, the latter composition is PE at 300 K). The author also reported a gradual decrease of oxygen ADPs from 300 to 427 K for SBN53, similar to the current study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The change in Nb ADPs is clearly associated with the paraelectric (PE) phase transition. Graetsch investigated the room-temperature structure of SBN with a wide composition range ( x = 0.32–0.82) and reported an U 33 increase of ∼0.03 Å 2 when comparing the structures of the FE and the RE compositions ( x = 0.69 and 0.81, respectively, the latter composition is PE at 300 K). The author also reported a gradual decrease of oxygen ADPs from 300 to 427 K for SBN53, similar to the current study.…”
Section: Resultsmentioning
confidence: 99%
“…Graetsch investigated the room-temperature structure of SBN with a wide composition range ( x = 0.32–0.82) and reported an U 33 increase of ∼0.03 Å 2 when comparing the structures of the FE and the RE compositions ( x = 0.69 and 0.81, respectively, the latter composition is PE at 300 K). The author also reported a gradual decrease of oxygen ADPs from 300 to 427 K for SBN53, similar to the current study. When heating CBN28 (Ca doped analogues) above the T c , U 33 of the respective Nb1 sites adapts a similar value (∼0.04 Å 2 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sr 0.52 Ba 0.48 Nb 2 O 6 crystals were grown according to the procedure of Whipps (1972) from a barium strontium tetraborate flux. A mixture of strontium carbonate, barium carbonate, niobium oxide and boric acid was melted in a Pt crucible at 1350 C and slowly cooled to 700 C at a rate of 5 C per hour followed by further cooling at a rate of 50 C h À1 to room temperature (Graetsch, 2014). The crystals were removed from the solidified flux by etching in hot dilute nitric acid.…”
Section: Crystal Growthmentioning
confidence: 99%
“…12 Recent structure refinement of a flux grown SBN53 (T C ≈ 368 K) has shown that at 600 K it can be still described in terms of a polar space group P4bm. 24 These uncertainties can be rationalized taking into account the fact that clusters of polarized NbO 6 chains have been shown to exist above the T C . 25 The chains produce strong diffuse scattering in the form of planes perpendicular to c * .…”
Section: Introductionmentioning
confidence: 99%